P2 domain profiles and shedding dynamics in prospectively monitored norovirus outbreaks - Sukhrie, Faizel H.A.; Teunis, Peter; Vennema, Harry; Bogerman, Jolanda; van Marm, Sebastian; Beersma, Matthias F.C. Thijs; Koopmans, Marion (Journal of clinical virology, 2013)
Norovirus P2 domain is commonly used to extrapolate transmission within an outbreak (OB) setting. The current definition is that transmission among cases is considered to be proven when no sequence variation is found. Previous studies have shown a high mutation rate and errors during replication of the norovirus genome, therefore the validity of this criterion must be evaluated. Sequences of the P2 domain were obtained from patients and health care workers sampled during 4 prospectively GII.4 outbreaks. Fecal samples were tested by RT-PCR for presence of norovirus RNA against a standard control preparation to allow quantification. Estimated time of onset of shedding was derived from shedding kinetics modeled on data from sequential sampling. Thereby P2 sequence variation could be linked to estimated total virus excretion in individual subjects. In all the outbreaks, P2 domain variation was found that resulted in unique codon changes in some patients. Mutations were found in 14% of initial samples and >50% of follow-up samples taken from patients involved in an outbreak. In three patients, aa mutations was observed in or near sites involved in host or antigen binding. We concluded that P2 domain variation increases with duration of virus shedding, but was unrelated to total amounts of virus shed. Therefore, we propose that cluster identification based on identical sequences should be relaxed to accommodate minor sequence variation. When using sequence data to support outbreak investigations, sequence diversity should be interpreted in relation to timing of sampling since onset of illness.